(untitled) - Oxtoby, David W. (Fort Worth, 1999)
The fourth edition of PRINCIPLES OF MODERN CHEMISTRY, which has dominated the honors and high mainstream general chemistry courses, is a substantial revision that maintains the rigor of previous editions but reflects the exciting modern developments taking place in chemistry today. The text provides a unique approach to learning chemical principles that emphasizes the total scientific process--from observation to application--placing general chemistry into a complete perspective for serious-minded science and engineering students. Chemical principles are illustrated by the use of modern materials, comparable to equipment found in the scientific industry. Students are therefore exposed to chemistry and its applications beyond the classroom. This text is perfect for those instructors who are looking for a more advanced general chemistry textbook.
Keywords: Chemistry,Hoá học